Perfecting of methods of supersonic inspection and structureskopy of foundry production in auto- and tractor-building - P. P. Prokhorenko; G. E. Konovalov; A. R. Baev; A. L. Majorov; P. S. Gurchenko; M. A. Tishchenko (Литьë и металлургия)
The results of investigation of methods of supersonic inspection and structureskopy of foundry production, being used in auto- and tractor-building are presented. On basis of using of conical waves there are given optimal schemas of quality control of gearing of Ni-resist insertion with material of diesel engine forcers directly in casting as well as in early stages of final processing.